AVO analysis for high amplitude anomalies using 2D pre-stack seismic data - Lamees Abdulkareem (Kuwait Journal of Science)
Amplitude variation with offset (AVO) analysis was applied on the 2D prestack data to confirm the AVO behaviour of the high amplitude anomalies or bright spots that have been interpreted as an indication of hydrocarbon leakage in the Laminaria High NW shelf of Australia. AVO cross plots from the real pre-stack seismic data show AVO class 4 as it gives a negative intercept decreasing with offset. This result matches our AVO result of fluid substitution for the seismic synthetics and we have a negative intercept decreasing with offset. From this result, it is concluded the high amplitude anomaly on the seabed and the target horizon 9 is the result of changing the fluid content and the lithology along the target horizons. It is noticed that changing the porosity has little effect on the amplitude variation with offset. Finally, a small change of thickness caused a change in the amplitude; however, this changing in thickness gives different AVO characteristic. Therefore, a thinner layer with changing fluids is more likely to be the cause of the high amplitude anomalies.